MFe2O4 and MFe@Oxide Core–Shell Nanoparticles Anchored on N‐Doped Graphene Sheets for Synergistically Enhancing Lithium Storage Performance and Electrocatalytic Activity for Oxygen Reduction Reactions. (2nd July 2013) - Xiao, Junwu; Xu, Guiliang; Sun, Shi‐Gang; Yang, Shihe
<x xml:space="preserve">Abstract</x> The intrinsically low electric conductivity and self‐aggregation of MFe2O4 during charge/discharge affect their lithium storage performance and electrocatalytic activity. To mitigate these problems, it is shown that N‐doped graphene sheets (NGS), as a highly conductive platform, finely disperse the MFe2O4 nanoparticles and rapidly shuttle electrons to and from the MFe2O4 nanoparticles. Moreover, by forming a metal@oxide core–shell nanostructure, fast electron transfer from the exterior oxide layer to NGS is achieved. Introducing NGS into MFe2O4 allows the composites to exhibit the comparable specific capacity (based on the total mass) to MFe2O4, although over 10 wt% of NGS contributes a low specific capacity of around 320–400 mAh g−1. More importantly, introducing NGS significantly increases the cycling stability performance: 97.5% (CoFe2O4/NGS) and ≈100% (NiFe2O4/NGS) of the specific capacities have been retained after 80 cycles, far higher than the capacity retentions of CoFe2O4 (35.3%) and NiFe2O4 (43.7%) tested under otherwise identical conditions. Also demonstrated are the excellent rate capabilities of the composites. For catalyzing the oxygen reduction reaction, the activity is significantly improved when the MFe2O4 nanoparticles are transformed into metal@oxide core–shell nanostructure, mainly because the core–shell nanostructure exhibits lower charge transfer resistance.